Erythrodermic psoriasis secondary to systemic corticosteroids. Issue 1 (2nd January 2020) - Heinrich, Matthew; Cook, Elizabeth; Roach, Jenna; Juarez, Rita Medrano; Payne, Drew; Atkins, Randy; Stetson, Cloyce
Abstract: Erythroderma is an uncommon, potentially life-threatening condition, which has many causes, including uncontrolled psoriasis. We present a 58-year-old woman with psoriasis who, after an abrupt discontinuation of systemic corticosteroids, developed erythrodermic psoriasis with extensive body surface involvement requiring hospital admission. Erythrodermic psoriasis requires a high index of suspicion to diagnose it in a timely fashion and treat it to prevent complications.